A Case Study on Philippine Sustainable Enterprises Aligned with the Quantum Sustainable Organizing Theory (QSOT) - Cheng, Angelique C. Blasa; Chiu, Rhett M.; Dy, Catherine M.; Kim, Su Jin; Trono, Paul D.; Aure, Patrick Adiel H.; Vergara, Raymond Allan (Future Science / FSH-PH Publications, 2023)
The research aims to build on Dyck and Greidanus’ (2016) study on the Quantum Sustainable Organizing Theory (QSOT) by analyzing Philippine sustainable enterprises and how they adopt and execute the principles of QSOT into their organization. The data gathered from the multiple-case study were collated and used to promote sustainability and build knowledge on the contemporary theory. The research utilized a qualitative embedded multiple-case study design in investigating the exhibition of QSOT in Philippine sustainable enterprises. Through in-depth interviews with three (3) Philippine sustainable enterprises or potentially QSOT organizations, the paper identified and illustrated QSOT-aligned business practices, operations, and functions. Among the three Philippine sustainable enterprises studied, two were identified as fully QSOT-oriented companies. The researchers note that QSOT can be operationalized in the country; however, the success of adoption and integration is dependent on the industry, ability to innovate the business structure, entanglement of “external” entities, and financial capacity. The study framed sustainable organizing practices in a manner that is concrete and specific—practices that enhance social and ecological well-being were elaborated. As the Quantum Sustainable Organizing Theory (QSOT) is a contemporary theory, more research is needed to understand the concept, especially in the Philippine context.